FIT ANALYSIS OF INDOSAT DOMPETKU BUSINESS MODEL USING A STRATEGIC DIAGNOSIS APPROACH - Fauzi Ridwansyah; Rina Oktaviani; Imam Teguh Saptono (Indonesian Journal of Business and Entrepreneurship (IJBE), 2015)
Mobile payment is an industry's response to global and regional technological-driven, as well as national social-economical driven in less cash society development. The purposes of this study were 1) identifying positioning of PT. Indosat in providing a response to Indonesian mobile payment market, 2) analyzing Indosat’s internal capabilities and business model fit with environment turbulence, and 3) formulating the optimum mobile payment business model development design for Indosat. The method used in this study was a combination of qualitative and quantitative analysis through in-depth interviews with purposive judgment sampling. The analysis tools used in this study were Business Model Canvas (MBC) and Ansoff’s Strategic Diagnosis. The interviewees were the representatives of PT. Indosat internal management and mobile payment business value chain stakeholders. Based on BMC mapping which is then analyzed by strategic diagnosis model, a considerable gap (>1) between the current market environment and Indosat strategy of aggressiveness with the expected future of environment turbulence level was obtained. Therefore, changes in the competitive strategy that need to be conducted include 1) developing a new customer segment, 2) shifting the value proposition that leads to the extensification of mobile payment, 3) monetizing effective value proposition, and 4) integrating effective collaboration for harmonizing company’s objective with the government's vision. Keywords: business model canvas, Indosat, mobile payment, less cash society, strategic diagnosis AbstrakMobile payment adalah sebuah respon industri terhadap dorongan teknologi global maupun regional, serta dorongan ekonomi nasional berupa pembentukan Masyarakat Non Tunai. Tujuan penelitian ini adalah 1) mengidentifikasi positioning PT. Indosat dalam memberikan respon terhadap pasar mobile payment di Indonesia, 2) menganalisis kesesuaian kapabilitas internal dan model bisnis mobile payment Indosat dengan turbulensi lingkungan, 3) memberikan rancangan pengembangan model bisnis mobile payment yang optimal bagi Indosat. Metode yang digunakan dalam penelitian ini adalah kombinasi analisis kualitatif dan kuantitatif melalui wawancara mendalam kepada narasumber ahli yang ditentukan secara purposive judgement sampling. Alat analisis yang digunakan dalam penelitian ini adalah Model Bisnis Kanvas (MBK) dan Strategic Diagnosis Ansoff. Narasumber penelitian adalah perwakilan manajemen internal PT. Indosat dan pihak-pihak pemangku kepentingan di dalam rantai nilai dasar bisnis mobile payment. Berdasarkan pemetaan MBK yang kemudian dianalisis dengan model strategic diagnosis menghasilkan adanya gap yang cukup jauh (>1) antara lingkungan pasar saat ini dan agresifitas strategi Indosat  dengan tingkat turbulensi lingkungan masa depan yang diharapkan. Oleh karena itu, perubahan strategi kompetitif yang perlu dilakukan adalah 1) membentuk segmen pelanggan baru, 2) melakukan pergeseran proposisi nilai yang mengarah kepada ekstensifikasi mobile payment, 3) monetisasi proposisi nilai yang efektif, dan 4) kolaborasi terpadu yang efektif untuk menyelaraskn tujuan perusahaan dengan visi pemerintah.Kata kunci: model bisnis kanvas, mobile payment, Indosat, masyarakat non tunai, strategic diagnosis